Effects of Visual Spatial Structure on Textual Conversational Multitasking. - Dresner, Eli; Barak, Segev (Communication Quarterly)
Textual computer-mediated communication gives rise to conversational multitasking — participation in several concomitant synchronous textual conversations. This study examined how this communication competence is affected by several visual parameters — the distance between conversation windows, number of windows, and window size. Results show that comprehension of concomitant textual conversations is not affected by the distance between conversation windows, and that the advantage of separating conversation threads into distinct windows is greater when overall window size is larger. This study considers the implications and applications of these results to communicative multitasking phenomena, in general, which become prevalent in technologically advanced societies. Reprinted by permission of the publisher.